PENGEMBANGAN SOAL STATISTIKA BERBASIS MICROSOFT POWER POINT VISUAL BASIC FOR APPLICATION (VBA) - Iesyah Rodliyah; Sari Saraswati (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2021)
The purpose of this study is to describe the results of the development of statistical questions presented by utilizing Microsoft Power Point applications based on Visual Basic for Applications. The development model in this study uses the ADDIE model which stands for analysis, design, development, implementation, and evaluation. This research trial used several subjects including two validators, namely material experts and media experts, as well as mathematics education students who took statistics courses. Data collection techniques were carried out through test and questionnaire methods. While the data analysis technique used quantitative descriptive analysis. This development research resulted in a product in the form of statistical test questions in the form of multiple choice questions consisting of five questions and packaged in a macro VBA-based Microsoft Power Point application. The results showed that the questions developed met the valid, reliable, and sensitive categories. In addition, the products developed have also met the criteria of being valid, practical, and effective for use.